Association of rs8444 polymorphism in the LASS2 3′-UTR and bladder cancer risk in Chinese population. Issue 4 (July 2020) - Huang, Yinglong; Wang, Haifeng; Fu, Shi; Luan, Ting; Zuo, Yigang; Li, Ning; Ding, Mingxia; Chen, Yujin; Wang, Jiansong
Abstract : The aim of the present study was to explore the correlations between single nucleotide polymorphisms in LASS2 gene 3′-untranslated regions and bladder cancer risk in Chinese population. We first performed PCR and sequence for LASS2-3′-UTR in 105 bladder cancer patients and 100 control subjects. Next, multivariate logistic regression analysis was used to determine the relationship between single nucleotide polymorphisms frequency and susceptibility of bladder cancer, and clinical features in 105 cases. In addition, survival curves and Cox Regression analysis were used to investigate the effect of single nucleotide polymorphisms on clinical outcome in 58 cases. Finally, quantitative reverse-transcription PCR and immunohistochemical were performed to explore the influence of single nucleotide polymorphisms on LASS2 expression. We found that a single nucleotide polymorphism (rs8444 C>T) located in the 3′-UTR of LASS2 was significantly associated with the risk of bladder cancer. We also showed the frequency of rs8444 T genotype was higher in bladder cancer group and correlated with the risk of clinical prognosis. Yet, there were no significant correlations between T/C allele frequencies and the distributions of rs8444 genotype and tumor-node-metastasis stage, histological grade and distant metastasis in bladder cancer. Furthermore, we demonstrated that rs8444 C>T could affect LASS2 expression by single nucleotide polymorphism-related mRNA stability. Our results showed that LASS2-3′-UTR rs8444 C>T polymorphism was significantly associated with the individual risk and the poor overall survival of bladder cancer, suggesting that rs8444 TT genotype maybe act as an independent risk factor of susceptibility and clinical prognosis for bladder cancer in Chinese population. Abstract : Supplemental Digital Content is available in the text.